(untitled) (Annals of Medical Research, 2022)
Aim: Angiopoetin-1 and Pentraxin-3 are new generation biomarkers in the inflammation pathway that have been studied in CKD and other inflammatory diseases. This study aims to investigate the relationship of Pentraxin-3 and Angiopoetin-1 in the inflammation pathway in chronic kidney disease (CKD). Materials and Methods: Our study was planned single-center, prospective, cross-sectional study. This study includes 25 healthy volunteers, 29 predialysis cases, 34 cases in routine hemodialysis program.Blood was drawn after 12 hours of fasting. In addition to routine biochemical tests, Pentraxin-3 Angiopoetin-1, 1,25 hydroxy Vitamin D levels were measured. Age and gender parameters, BUN, creatinine, e-GFR values of the cases were recorded. Results: Pentraxin-3 levels were not statistically significant for all three groups (p=0.993).For angiopoietin-1 levels, statistical significance was found between all three groups (p<0.001).While 25 hydroxy Vit D levels were not statistically significant between all three groups (p=0.329), by comparison with 1.25 dihydroxy Vit D levels, a statistically significant difference was found for all three groups (p<0.001). There was a positive low-level relationship (r=0.023) between creatine and Pentraxin-3, and this relationship was not statistically significant (p=0.832).There is a moderate positive correlation (r=0.593) between creatine and angiopoietin-1 and this relation is statistically significant (p<0.001). A simple regression model was established for creatine and angiopoietin-1. Conclusion: Since Pentraxin-3 is accepted as an acute phase reactant in the literature, no significant relationship was found between all groups in our study either. Angiopoietin -1 levels were found to be increased in CKD cases and we found statistically significant results. Angiopoetin -1 can be considered as a useful biomarker for the follow-up and treatment of CKD.